Imaging clinical case - Martins, Cristiana (2019)
Introduction: Acute hemorrhagic edema of infancy (AHEI) is a rare and benign leukocytoclastic vasculitis, frequently misdiagnosed. Case report: A twelve-month-old boy presented with a seven-day history of coryza and cough associated with lowgrade fever and the sudden appearance of a purpuric rash over the left lower limb. It progressed to an annular purpuric rash, with well-defined edges, on the face, limbs, ears, buttocks, and scrotum, with right tibiotarsal joint edema. Mild thrombocytosis was detected on laboratorial investigation. Patient was treated with a two-day course of oral betamethasone, with clinical improvement. No complications were reported within three weeks of follow-up. Discussion: AHEI has a sudden onset and a benign, self-limiting course. This report may be a helpful reminder to discriminate AHEI from other, more serious diseases, avoiding exhaustive and unnecessary investigation.